7(x-7)+x=8(x-7)+7

Simple and best practice solution for 7(x-7)+x=8(x-7)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-7)+x=8(x-7)+7 equation:


Simplifying
7(x + -7) + x = 8(x + -7) + 7

Reorder the terms:
7(-7 + x) + x = 8(x + -7) + 7
(-7 * 7 + x * 7) + x = 8(x + -7) + 7
(-49 + 7x) + x = 8(x + -7) + 7

Combine like terms: 7x + x = 8x
-49 + 8x = 8(x + -7) + 7

Reorder the terms:
-49 + 8x = 8(-7 + x) + 7
-49 + 8x = (-7 * 8 + x * 8) + 7
-49 + 8x = (-56 + 8x) + 7

Reorder the terms:
-49 + 8x = -56 + 7 + 8x

Combine like terms: -56 + 7 = -49
-49 + 8x = -49 + 8x

Add '49' to each side of the equation.
-49 + 49 + 8x = -49 + 49 + 8x

Combine like terms: -49 + 49 = 0
0 + 8x = -49 + 49 + 8x
8x = -49 + 49 + 8x

Combine like terms: -49 + 49 = 0
8x = 0 + 8x
8x = 8x

Add '-8x' to each side of the equation.
8x + -8x = 8x + -8x

Combine like terms: 8x + -8x = 0
0 = 8x + -8x

Combine like terms: 8x + -8x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 6y+21=3x | | 4y=8x-24 | | 3x-15=-33 | | -4(x-7)-8=20 | | 86-(6x+5)=6(x+7)+x | | 4q+q^2+4=25 | | -4=8y-9y+6 | | 13-2x=x-9+4 | | 1.6(8-x)=1.4(6-x) | | 6y+y^2+9=49 | | 0q^2+4q+4=25 | | 7m+42=0 | | x^2-12x=-32 | | -16t^2+80t=96 | | 2(3x+9)=66 | | 5(6x-5)=35 | | -6(4+x)=-84 | | -4(1x+1)=-44 | | x^6-2x^3-48= | | 4h-9h+3=32 | | 8x^2+19x-15=0 | | 3(2x+8)=66 | | 4h-9h=32 | | 5b^3+15b+12b=-36 | | 4x^2+21x-49=0 | | 5(x+8)+6=5x+9 | | 4x-10=0 | | 1-2k=-9 | | 5b^3+15b=-36 | | 9(n+2)=3(6+3n) | | 5(4x+10)=170 | | -4(-7+4x)=188 |

Equations solver categories